Preparation method and application of thermochromic film based on hollow VO2 nanoparticles

The hollow VO2 nano powder below 100 nm was prepared by the template method and applied to glass or flexible substrate, which solved the problems of high refractive index and excessive particle size of the VO2 film, and achieved the high transmittance and multifunctionality of the thermochromic film Thermal performance meets the needs of intelligent energy-saving windows.

CN112646566BActive Publication Date: 2024-12-20NINGBO YONGAN OPTICAL NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202011386459.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-12-01
Publication Date
2024-12-20
Estimated Expiration
2040-12-01

AI Technical Summary

Technical Problem

The existing VO2 film has a high refractive index, resulting in insufficient transparency, which limits its application in the field of intelligent energy-saving windows. The hollow VO2 nanoparticle size is too large to meet the requirements below 100nm and cannot be effectively used in intelligent energy-saving windows.

Method used

The hollow VO2 nano powder below 100 nm was prepared by template method, and the coating liquid was formed by dispersing it into an organic solvent or resin, and applied to glass or flexible substrate to prepare a thermochromic film, which was heat-treated by high temperature heat treatment. A hollow VO2 nano powder was obtained.

Benefits of technology

Thermal colored film of hollow VO2 nanoparticles below 100nm was achieved on glass and flexible substrates, which improved transmittance, especially at low temperatures with high heat transmission capacity, high heat barrier properties at high temperatures, and expanded the application range. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112646566B_ABST
    Figure CN112646566B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a thermochromic film based on hollow VO2 nanoparticles below 100 nm on a glass substrate and a flexible substrate and its application, as well as a method for preparing hollow VO2 nanoparticles below 100 nm. The hollow VO2 nanoparticles below 100 nm can be stacked and then applied to a glass substrate; the hollow VO2 nanoparticles below 100 nm can also be dispersed in a resin and applied to a flexible substrate, so that the application range of the thermochromic film is wider; the thermochromic film prepared as above can achieve good performance in infrared invisible light, ensuring that it has high heat transmission ability at low temperature and high heat blocking ability at high temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method and application for preparing a thermochromic film based on hollow VO2 nanoparticles below 100nm on a glass substrate and a flexible substrate, and a method for preparing hollow VO2 nanoparticles below 100nm. Background Art

[0002] According to statistics, with energy becoming increasingly scarce today, building energy consumption accounts for one-third of total human energy consumption, and nearly half of building energy consumption is indirectly generated through windows. With the continuous development of science and technology, the emergence of smart energy-saving windows has improved this phenomenon. Smart energy-saving windows can automatically adjust the transmittance of sunlight, making the room warm in winter and cool in summer, reducing the use of temperature control equipment and playing a role in saving energy.

[0003] Smart energy-saving windows use materials with variable optical properties, and use their response to light, electricity, gas or heat to produce chemical changes or phase changes, thereby achieving the purpose of intelligently adjusting the indoor ambient temperature. Vanadium dioxide is a typical thermochromic material with a phase change temperature of 68°C. Because its optical properties change significantly before and after the phase change, and the phase change temperature is closer to room temperature, it is widely used in automobiles, buildings, spacecraft and other fields to achieve automatic indoor temperature adjustment.

[0004] At present, the main preparation methods of VO2 thin films include magnetron sputtering, pulsed laser deposition, chemical vapor deposition (CVD), sol-gel, hydrothermal method, etc. However, the dense VO2 thin films prepared by the above methods have a high refractive index and low visible light transmittance, resulting in insufficient visual transparency, which is also one of the main reasons limiting its application. In order to solve this problem, the main method is to coat a layer of low refractive index film on the outside of the VO2 thin film to construct a multilayer film, or to regulate the VO2 microstructure to reduce its refractive index. Synthesizing hollow VO2 nanoparticles is one of the important methods to reduce the refractive index of inorganic oxides.

[0005] The particle size of hollow VO2 nanoparticles determines their application in the field of smart energy-saving windows. If the particle size is too large, it cannot be used. At present, the particle size of hollow VO2 is several microns, which cannot meet the requirement of particle size less than 100nm in the field of smart energy-saving windows. Therefore, it is necessary to develop a method to prepare hollow VO2 nanoparticles below 100nm.

[0006] At present, the methods for preparing inorganic hollow spheres mainly include the following categories: (1) template method; (2) emulsion method; (3) micelle self-assembly method; (4) spray reaction method; (5) synthesis using the Ostwald ripening mechanism. The template method refers to first controlling the deposition or reaction of the precursor on the surface of the template sphere to form a surface coating layer; then removing the template by dissolving, heating or chemical reaction to obtain a micro / nano hollow sphere structure. The template method for preparing inorganic hollow spheres has the advantage of controllable size, and its particle size is close to the template particle size. It is one of the methods for preparing small-diameter hollow nanospheres. Summary of the invention

[0007] In view of the current status of the above-mentioned prior art, the present invention is to be able to prepare a thermochromic film based on hollow VO2 nanoparticles on a glass substrate and a flexible substrate, thereby providing a preparation method and application of a thermochromic film based on hollow VO2 nanoparticles.

[0008] The technical solution adopted by the present invention to solve the above technical problems is:

[0009] A thermochromic film based on hollow VO2 nanoparticles with a diameter of less than 100 nm for a glass substrate, wherein the film is composed of a stack of hollow VO2 nanoparticles with a diameter of less than 100 nm, and the glass substrate is K9 glass, quartz glass, or ultra-white glass. The preparation method thereof comprises the following steps:

[0010] (1) Dispersing hollow VO2 nanopowder into an organic solvent, adding a film-forming agent, and stirring at room temperature for a period of time to form a coating liquid;

[0011] (2) The coating liquid is coated on a glass substrate, and dried at 50-100° C. for 5-10 minutes to obtain the film.

[0012] Preferably, in step (1), the organic solvent is one or more of ethanol, propanol, isopropanol, and ethyl acetate, the mass fraction of hollow VO2 in the coating solution is between 1% and 10%, and the film-forming agent is polyvinyl pyrrolidone.

[0013] Preferably, in step (2), the coating method is one of Czochralski coating, spin coating and spray coating.

[0014] Preferably, the film is formed by dispersing hollow VO2 nanoparticles with a size of less than 100 nm into a resin and then coating the resin onto a flexible substrate.

[0015] Preferably, the resin is one or more of polyurethane resin, acrylic resin, vinyl resin, and epoxy resin, and the flexible substrate is one of polyethylene terephthalate PET, polycarbonate PC, and polymethyl methacrylate PMMA.

[0016] A thermochromic film based on hollow VO2 nanoparticles with a diameter of less than 100 nm for a flexible substrate, wherein the preparation method comprises the following steps:

[0017] (1) The hollow VO2 nanopowder is dispersed in a solvent, and then a resin is added in a certain mass ratio, and a corresponding initiator is added according to the type of resin to form a coating liquid.

[0018] (2) Applying the coating in step (1) onto a flexible substrate, and curing the resin to obtain the flexible hollow VO2 thermochromic film.

[0019] Preferably, the solvent in step (1) is one or more of deionized water, ethyl acetate, ethanol, and propanol, the mass fraction of the hollow VO2 nanopowder in the solvent is 1%-20%, the mass ratio of the hollow VO2 nanopowder to the resin is 1:100-30:100, the initiator is one or more of benzil, alkyl phenone, and benzophenone, and the curing method in step (2) is one or more of room temperature curing, thermal curing, and ultraviolet light curing.

[0020] By adopting the above technical scheme, the hollow VO2 nanopowder prepared by the present invention can be directly coated on a glass substrate to form a thermochromic film, and can also be mixed with resin and other materials and then coated on a flexible substrate, so that the application range of the thermochromic film is more extensive.

[0021] A method for preparing hollow VO2 nanopowders with a diameter of less than 100 nm, comprising the following steps:

[0022] (1) Preparation of polymer nanoparticles as templates: Deionized water is heated to 50-90°C and protected by nitrogen. The polymer monomer is added under high-speed stirring. After stirring for 1-10 minutes, an aqueous solution of anionic initiator is added dropwise for 1-5 minutes. After the addition is completed, the reaction is carried out for 3-10 minutes, and then the mixture is quickly cooled with ice water.

[0023] (2) Preparation of polymer beads @ VO(OH)2 core-shell particles: Add VO(OH)2 to the liquid obtained in step (1) dropwise under high-speed stirring. 2+ The aqueous solution of ions is stirred for 30-120 minutes, and then a pH regulator is added dropwise to adjust the pH value of the solution, VO(OH)2 is deposited on the surface of the template to synthesize VO(OH)2, and then filtered and washed to obtain polymer beads@VO(OH)2 core-shell nanopowders.

[0024] (3) Removing polymer beads: Disperse the polymer beads@VO(OH)2 core-shell nanopowder into a good solvent of the polymer template, stir for 2 to 4 hours, and then let stand for 12 to 24 hours to allow the layers to separate. The lower layer is hollow VO(OH)2 nanoparticles and the upper layer is a polymer solution. Remove the upper layer solution and repeat this step 3-4 times.

[0025] (4) subjecting the hollow VO(OH)2 nanoparticles to high-temperature heat treatment under the protection of an inert gas to obtain the hollow VO2 nanopowder.

[0026] Preferably, the polymer monomer in step (1) is one or a mixture of methyl methacrylate (MMA) and styrene (St), the concentration of the polymer monomer in distilled water is between 0.1 and 0.5 mol / L, the stirring and dispersion time after adding the monomer is 1 to 10 min, the anionic initiator is one or more of potassium persulfate, butyl lithium, potassium amide, sodium hydroxide, potassium hydroxide, the molar ratio of the initiator to the polymer monomer is 1:50 to 1:200, and the VO-containing 2+ The aqueous solution of ions is one of VOSO4 aqueous solution and VOCl2 aqueous solution, the pH regulator is one of ammonia water, sodium hydroxide, potassium hydroxide, and lithium hydroxide, the pH of the solution is 8-10, the solvent in step (3) is one or more of ethyl acetate, toluene, phenol, and anisole, and the heat treatment temperature in step (4) is 300-700°C.

[0027] Compared with the prior art, the advantages of the present invention are:

[0028] By adopting the above technical solution, the particle size of the hollow VO2 nanopowder prepared based on the template method is below 100nm, and the thermochromic film made of the hollow VOVOSO4 nanopowder below 100nm can be applied to both glass substrates and soft substrates, with a wide range of applications.

[0029] When the wavelength is between 300 and 760 nm, the transmittance of the thermochromic film on the glass substrate and the thermochromic film on the flexible substrate increases with the lengthening of the wavelength, and the transmittance of visible light is also improved; when the wavelength is greater than 760 nm, the transmittance of the thermochromic film on the glass substrate and the thermochromic film on the flexible substrate changes, and the transmittance of the thermochromic film at 20°C is significantly higher than that at 95°C, thereby ensuring that it has high heat transmission ability at low temperatures and high heat blocking ability at high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1The SEM image of polymer bead template P(MMA+St) nanoparticles prepared using methyl methacrylate (MMA) and styrene (St) monomers;

[0031] Figure 2 TEM image of P(MMA+St)@VO(OH)VOSO4 core-shell nanoparticles prepared using VOSO4 and ammonia water;

[0032] Figure 3 TEM image of hollow VO2 nanoparticles;

[0033] Figure 4 This is the XRD pattern of hollow VO2 nanoparticles;

[0034] Figure 5 The transmittance curve of the thermochromic film prepared by dispersing hollow VO2 nanoparticles in ethanol and then coating on quartz glass;

[0035] Figure 6 The transmittance curve of the thermochromic film prepared by dispersing hollow VO2 nanoparticles in ethanol and then coating on K9 glass;

[0036] Figure 7 The transmittance curve of the thermochromic film prepared by dispersing hollow VO2 nanoparticles in ethanol and then coating on ultra-white glass;

[0037] Figure 8 The transmittance curve of the flexible thermochromic film prepared by mixing hollow VO2 nanoparticles and acrylic resin and coating them on a PET substrate;

[0038] Fig. 9 The transmittance curve of the flexible thermochromic film prepared by mixing hollow VO2 nanoparticles and acrylic resin and coating them on a PC substrate;

[0039] Fig.10 This is the transmittance curve of the flexible thermochromic film prepared by mixing hollow VO2 nanoparticles and acrylic resin and coating them on a PMMA substrate. DETAILED DESCRIPTION

[0040] like Figures 1 to 10 As shown, the present invention discloses a method and application of a thermochromic film based on hollow VO2 nanoparticles below 100 nm, as well as a method for preparing hollow VO2 nanoparticles below 100 nm.

[0041] The method for preparing the thermochromic film based on hollow VO2 nanoparticles below 100 nm for glass substrate in the present invention is as follows:

[0042] 1. Prepare hollow VO2 coating liquid

[0043] 1.1 Materials: hollow VO2 nanopowder, ethanol, polyvinyl pyrrolidone (PVP);

[0044] 1.2 Method: Disperse hollow VO2 nanopowder into ethanol solvent with a mass fraction of 1-5wt%, stir for 30-60min, add 0.2-0.5wt% PVP to improve the film-forming property of the coating solution, and stir for 1h to obtain the coating solution.

[0045] 2. Coating of hollow VO2 thermochromic film

[0046] Before coating, quartz glass, K9 glass and ultra-white glass are placed in ethanol for ultrasonic treatment for 10 minutes, and the glass substrate is placed in the hollow VO2 coating liquid. The coating is pulled at a speed of 50-300mm / min. After coating, it is placed in a 60°C oven for 5-10 minutes to completely remove the solvent to obtain a thermochromic film.

[0047] The preparation method of the flexible thermochromic film based on hollow VO2 nanoparticles below 100nm for a flexible substrate in the present invention is as follows:

[0048] 1. Prepare coating solution

[0049] 1.1 Materials: hollow VO2 nanopowder, ethyl acetate, acrylic resin, initiator 1-hydroxycyclohexyl phenyl ketone;

[0050] 1.2 Method: Disperse the hollow VO2 nanopowder in ethyl acetate solvent with a mass fraction of 1-5wt%, and stir for 60-120min; take 100ml of the dispersion, add 5-15g of acrylic resin and stir for 60-120min, and finally add 0.1-0.3g of initiator and stir for 60-120min to obtain the coating solution.

[0051] 2. Preparation of flexible hollow VO2 thermochromic film

[0052] The mixed coating liquid of the above hollow VO2 and acrylic resin is respectively coated on polyethylene terephthalate PET, polycarbonate PC, and polymethyl methacrylate PMMA flexible substrates by roller coating, and then the resin is cross-linked and cured using UV light to obtain a flexible hollow VO2 thermochromic film.

[0053] The present invention provides a method for preparing hollow VO2 nanopowders with a diameter of less than 100 nm, as follows:

[0054] 1. Preparation of polymer ball template

[0055] 1.1 Materials: deionized water, methyl methacrylate (MMA), styrene (St) monomer, potassium persulfate;

[0056] 1.2 Method: Take a certain amount of deionized water and heat it to 80°C, and pass nitrogen protection, add polymer monomer methyl methacrylate and polymer monomer styrene into it under high-speed stirring, the MMA / St molar ratio is 1-3, and continue stirring, the concentration of polymer monomer in deionized water is 0.2-0.6 mol / L, take potassium persulfate anion initiator and dissolve it in a certain amount of deionized water, the molar ratio of initiator to polymer monomer is 0.005-0.02, after stirring for 2 minutes, add potassium persulfate aqueous solution dropwise, the addition time is 1-5 minutes, continue to react for 5-10 minutes after the addition is completed, and the reaction container is quickly cooled with ice water to terminate the reaction.

[0057] 2. Preparation of hollow VO(OH)2 nanopowder

[0058] 2.1 Materials: deionized water, VOSO4, ammonia, toluene

[0059] 2.2 Method: Dissolve VOSO4 in deionized water at a concentration of 0.2-1 mol / L. Add the VOSO4 aqueous solution dropwise to the P(MMA+St) dispersion under high-speed stirring. The volume ratio of the two is 1:1-1:3. Stir for 2-4 hours. Since an anionic initiator is used to prepare P(MMA+St), its surface is negatively charged. After adding VOSO4, the surface of the P(MMA+St) template will adsorb VO 2+ ions, and then pH regulator ammonia was added dropwise to adjust the pH value of the reaction system to 8-10, and VO adsorbed on the template surface 2+ Ions and OH - Ion reaction generates VO(OH)2 on the template surface to obtain P(MMA+St)@VO(OH)2 core-shell nanopowder;

[0060] The above core-shell nanopowder is dispersed in a good solvent, toluene, and stirred. Toluene will dissolve the P(MMA+St) core in the core-shell structure to obtain VO(OH)2 hollow nanoparticles. The solution is then allowed to stand. Since the VO(OH)2 hollow nanoparticles are heavier, they will settle to the lower layer of the solution during the standing process. The upper layer is the P(MMA+St) solution. The upper layer of the solution is removed and this step is repeated 3-4 times. The P(MMA+St) can be completely removed to obtain VO(OH)2 hollow nanopowder.

[0061] 3. Preparation of hollow VO2 nanopowder

[0062] 3.1 Materials: Rotary tube furnace, Ar gas

[0063] 3.2 Method: The hollow VO(OH)2 nanopowder is placed in a rotatable tube furnace and subjected to high-temperature heat treatment under Ar gas protection to obtain the hollow VO2 nanopowder. The heat treatment temperature is 300-700C and the heat treatment time is 30min.

[0064] Thermochromic performance test of thermochromic film based on hollow VO2 nanoparticles below 100nm in the present invention:

[0065] 1. Testing instrument: UV-visible spectrometer; model: Hitachi U4100; homemade film heating device;

[0066] 2. Detection method: The thermochromic films on glass substrates and flexible substrates obtained in the above experiments were tested in the wavelength range of 300-2500nm and the test temperatures of 20℃ and 95℃;

[0067] 3. The thermochromic properties of the film can be characterized by measuring the transmittance curves at 20°C and 95°C. Figure 5-Figure 10 As shown, Figure 5 The transmittance curve of the thermochromic film prepared by dispersing hollow VO2 nanoparticles in ethanol and then coating on quartz glass; Figure 6 The transmittance curve of the thermochromic film prepared by dispersing hollow VO2 nanoparticles in ethanol and then coating on K9 glass; Figure 7 The transmittance curve of the thermochromic film prepared by dispersing hollow VO2 nanoparticles in ethanol and then coating on ultra-white glass; Figure 8 The transmittance curve of the flexible thermochromic film prepared by mixing hollow VO2 nanoparticles and acrylic resin and coating them on a PET substrate; Fig. 9 The transmittance curve of the flexible thermochromic film prepared by mixing hollow VO2 nanoparticles and acrylic resin and coating them on a PC substrate; Fig.10 The transmittance curve of the flexible thermochromic film prepared by mixing hollow VO2 nanoparticles and acrylic resin and coating them on PMMA substrate;

[0068] It can be seen from the picture that when the wavelength is 300-760nm, the transmittance of the thermochromic film used on the glass substrate and the thermochromic film used on the flexible substrate increases with the increase of the wavelength, and the transmittance of visible light is also improved; when the wavelength is greater than 760nm, the transmittance of the thermochromic film used on the glass substrate and the thermochromic film used on the flexible substrate both changes, and the transmittance of the thermochromic film at 20°C is significantly higher than the transmittance at 95°C, thereby ensuring that it has high heat transmission ability at low temperatures and high heat blocking ability at high temperatures.

[0069] Morphology and phase analysis of hollow VO2 nanoparticles below 100nm of the present invention:

[0070] 1. Testing instruments: scanning electron microscope SEM (Hitachi S4800, operating voltage is 10 kV), transmission electron microscope (TEM, JEM-2100, JEOL, operating voltage is 200 kV) and X-ray diffraction (XRD, Bruker D8 Advance A25, Co target, λKα1=1.78897 Å, 0.02 mm Fe filter);

[0071] 2. Test method: drop the prepared polymer ball dispersion on the surface of silicon wafer, and perform SEM test to characterize its particle size after drying. Drop the hollow VO(OH)2 ball dispersion and hollow VO2 dispersion drop 1 on ordinary carbon support film, and perform TEM test to characterize its morphology after drying. Perform XRD test on hollow VO2 powder to characterize its crystal structure.

[0072] 3. SEM photos of P(MMA+St) pellets are shown below: Figure 1 As shown in the figure, the particle size of P(MMA+St) spheres is uniform and less than 100 nm. The TEM images of hollow VO(OH)2 spheres and hollow VO2 nanospheres are shown in the figure. Figure 2 and Figure 3 As shown in Figure 2, the particle size is below 100nm and the wall thickness is about 10nm; the XRD test results of VO2 nanopowder are shown in Figure 2. Figure 4 As shown, all diffraction peaks are monoclinic phase (M phase) VO2 (corresponding to JCPDS NO. 72-0514), and no other diffraction peaks appear.

[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A hollow VO based on 100nm or less for glass substrate 2 Thermochromic film of nanoparticles, the film is composed of hollow VO with a diameter of less than 100 nm 2 The glass substrate is composed of nanoparticles, and is K9 glass, quartz glass, or ultra-white glass; A hollow VO with a thickness below 100nm 2 The method for preparing nano powder comprises the following steps: (1) Preparation of polymer nanoparticles as templates: Deionized water is heated to 50-90°C and nitrogen is passed through it, and polymer monomers are added under high-speed stirring. After stirring for 1-10 minutes, an aqueous solution of anionic initiator is added dropwise for 1-5 minutes. After the addition is completed, the reaction is carried out for 3-10 minutes, and then the mixture is quickly cooled with ice water; (2) Preparation of polymer beads @VO(OH) 2 Core-shell particles: Add VO2+ dropwise to the liquid obtained in step (1) under high-speed stirring. 2+ The aqueous solution of ions is stirred for 30-120 minutes, and then the pH regulator is added dropwise to adjust the pH value of the solution, and VO(OH) is deposited on the template surface to synthesize 2 , and filtered and washed to obtain polymer beads @VO(OH) 2 Core-shell nanopowders; (3) Removing polymer beads: Removing the polymer beads @VO(OH) 2 The core-shell nanopowder is dispersed in a good solvent of the polymer template, stirred for 2 to 4 hours, and then allowed to stand for 12 to 24 hours to separate into layers. The lower layer is hollow VO(OH) 2 Nanoparticles, the upper layer is polymer solution, remove the upper solution, and repeat this step 3-4 times; (4) The above hollow VO(OH) 2 The nanoparticles are subjected to high temperature heat treatment under inert gas protection to obtain the hollow VO 2 Nano powder; The polymer monomer in step (1) is one or a mixture of methyl methacrylate (MMA) and styrene (St), the concentration of the polymer monomer in distilled water is between 0.1 and 0.5 mol / L, the stirring and dispersion time after adding the monomer is 1 to 10 min, the anionic initiator is one or more of potassium persulfate, butyl lithium, potassium amide, sodium hydroxide, potassium hydroxide, the molar ratio of the initiator to the polymer monomer is 1:50 to 1:200, and the VO-containing 2+ The aqueous solution of ions is VOSO 4 Aqueous solution and VOCl 2 The pH regulator is one of aqueous solutions, wherein the pH regulator is one of ammonia water, sodium hydroxide, potassium hydroxide, and lithium hydroxide, the pH of the solution is 8 to 10, the solvent in step (3) is one or more of ethyl acetate, toluene, phenol, and anisole, and the heat treatment temperature in step (4) is 300 to 700° C.; The method for preparing a thermochromic film comprises the following steps: (1) Hollow VO 2 The nanopowder is dispersed in an organic solvent, a film-forming agent is added, and the mixture is stirred at room temperature for a period of time to form a coating liquid; (2) The coating liquid is coated on a glass substrate, and dried at 50-100° C. for 5-10 minutes to obtain the film.

2. A hollow VO based on 100nm or less for glass substrate according to claim 1. 2 Thermochromic film of nanoparticles, in step (1), the organic solvent is one or more of ethanol, propanol, isopropanol, ethyl acetate, the coating liquid has hollow VO 2 The mass fraction of is between 1% and 10%, and the film-forming agent is polyvinyl pyrrolidone.

3. A hollow VO based on 100nm or less for glass substrate according to claim 2. 2 In the step (2) of the thermochromic film of nanoparticles, the coating method is one of the following: Czochralski coating, spin coating, and spray coating.

4. A 100nm or less hollow VO for flexible substrates 2 Thermochromic film of nanoparticles, wherein the film is hollow VO with a diameter of less than 100 nm 2 The nanoparticles are dispersed in a resin and then coated on a flexible substrate; A hollow VO with a thickness below 100nm 2 The method for preparing nano powder comprises the following steps: (1) Preparation of polymer nanoparticles as templates: Deionized water is heated to 50-90°C and nitrogen is passed through it, and polymer monomers are added under high-speed stirring. After stirring for 1-10 minutes, an aqueous solution of anionic initiator is added dropwise for 1-5 minutes. After the addition is completed, the reaction is carried out for 3-10 minutes, and then the mixture is quickly cooled with ice water; (2) Preparation of polymer beads @VO(OH) 2 Core-shell particles: Add VO2+ dropwise to the liquid obtained in step (1) under high-speed stirring. 2+ The aqueous solution of ions is stirred for 30-120 minutes, and then the pH regulator is added dropwise to adjust the pH value of the solution, and VO(OH) is deposited on the template surface to synthesize 2 , and filtered and washed to obtain polymer beads @VO(OH) 2 Core-shell nanopowders; (3) Removing polymer beads: Removing the polymer beads @VO(OH) 2 The core-shell nanopowder is dispersed in a good solvent of the polymer template, stirred for 2 to 4 hours, and then allowed to stand for 12 to 24 hours to separate into layers. The lower layer is hollow VO(OH) 2 Nanoparticles, the upper layer is polymer solution, remove the upper solution, and repeat this step 3-4 times; (4) The above hollow VO(OH) 2 The nanoparticles are subjected to high temperature heat treatment under inert gas protection to obtain the hollow VO 2 Nano powder; The polymer monomer in step (1) is one or a mixture of methyl methacrylate (MMA) and styrene (St), the concentration of the polymer monomer in distilled water is between 0.1 and 0.5 mol / L, the stirring and dispersion time after adding the monomer is 1 to 10 min, the anionic initiator is one or more of potassium persulfate, butyl lithium, potassium amide, sodium hydroxide, potassium hydroxide, the molar ratio of the initiator to the polymer monomer is 1:50 to 1:200, and the VO-containing 2+ The aqueous solution of ions is VOSO 4 Aqueous solution and VOCl 2 The pH regulator is one of aqueous solutions, wherein the pH regulator is one of ammonia water, sodium hydroxide, potassium hydroxide, and lithium hydroxide, the pH of the solution is 8 to 10, the solvent in step (3) is one or more of ethyl acetate, toluene, phenol, and anisole, and the heat treatment temperature in step (4) is 300 to 700° C.; Thermochromic film, the preparation method thereof comprises the following steps: (1) Hollow VO 2 The nanopowder is dispersed in the solvent, and then the resin is added in a certain mass ratio, and the corresponding initiator is added according to the type of resin to form a coating liquid; (2) applying the coating solution in step (1) onto a flexible substrate, and curing the resin to obtain the flexible hollow VO 2 Thermochromic films.

5. A method for a flexible substrate based on a hollow VO with a thickness of less than 100 nm according to claim 4. 2 The thermochromic film of nanoparticles, the resin is one or more of polyurethane resin, acrylic resin, vinyl resin, epoxy resin, and the flexible substrate is one of polyethylene terephthalate PET, polycarbonate PC, and polymethyl methacrylate PMMA.

6. A method for a flexible substrate based on a hollow VO with a thickness of less than 100 nm according to claim 5 2 Thermochromic film of nanoparticles, the solvent in step (1) is one or more of deionized water, ethyl acetate, ethanol, propanol, the hollow VO 2 The mass fraction of the nanopowder in the solvent is 1%-20%, the mass ratio of the hollow VO2 nanopowder to the resin is 1:100-30:100, the initiator is one or more of benzil, alkylphenone, and benzophenone, and the curing method in step (2) is one or more of room temperature curing, heat curing, and ultraviolet light curing.

Citation Information

Patent Citations

  • Vo2 carrying hollow particle having thermochromic property and manufacturing method therefor

    JP2019064881A

  • Method for producing vanadium dioxide-containing particles, vanadium dioxide-containing particles, dispersion, and optical film

    WO2016017611A1